Criminology Goes to the Movies Crime Theory and Popular Culture - Rafter, Nicole; Brown, Michelle (New York University Press, 2011)
Investigating cinema under the magnifying glassFrom a look at classics like Psycho and Double Indemnity to recent films like Traffic and Thelma & Louise, Nicole Rafter and Michelle Brown show that criminological theory is produced not only in the academy, through scholarly research, but also in popular culture, through film. Criminology Goes to the Movies connects with ways in which students are already thinking criminologically through engagements with popular culture, encouraging them to use the everyday world as a vehicle for theorizing and understanding both crime and perceptions of criminality. The first work to bring a systematic and sophisticated criminological perspective to bear on crime films, Rafter and Brown’s book provides a fresh way of looking at cinema, using the concepts and analytical tools of criminology to uncover previously unnoticed meanings in film, ultimately making the study of criminological theory more engaging and effective for students while simultaneously demonstrating how theories of crime circulate in our mass-mediated worlds. The result is an illuminating new way of seeing movies and a delightful way of learning about criminology. Instructor's Guide